Report from the International Conference on Architectural Culture and Society & Housing London (United Kingdom), 29-30 November 2019 - Adamczewski, Jakub (Studia Edukacyjne, 2019)
Report from the International Conferencen on Architectural Culture and Society & Housing London (United Kingdom), 29-30 November 2019